Military Law practitioners and academic discourse: A Sine Qua Non for developing Military Law - Nel, Michelle (Scientia Militaria - South African Journal of Military Studies, 2017)
There has been limited development in South African military law since the inception of the Union Defence Force in 1912. Military law has mainly evolved as a way to enforce discipline in a force consisting of mostly conscripted members and a historical comparison of the relevant legislation shows no renewal in military justice or its processes in spite of a shift to a new all-volunteer force. Surely the approach towards discipline and military justice should also change. However, the limited development seen since was only brought about when necessitated by Constitutional challenges and external factors. This also seems true for the military law practitioners’ understanding of what military law entails. Generally military law is understood as the criminal law of the soldier, limiting it to the realm of military justice. Considering the expanding role of armed forces internationally, and the secondary roles of its employment, there is a clear need for a broadening of the definition and scope of military law as a discipline. The author argues that there are a number of other disciplines that can be of great assistance in a broadening of our understanding of military law. This article therefore argues that there is a critical need to develop military law as well as our understanding of what is entails. This then requires the development of a legal-academic discourse within the discipline.